TEACHERS’ SENSE OF EFFICACY AND IMPLICATIONS FOR IMPLEMENTATION OF INCLUSIVE EDUCATION - Ilić-Stošović, Danijela; Nikolić, Snežana; Popadić, Mirjana (Specijalna edukacija i rehabilitacija, 2015)
Numerous studies confirm that self-efficacy positively correlates with teachers’ readiness to accept innovations in teaching and meet students’ needs, and with their satisfaction and performance at work. The aim of this research is to examine teachers’ sense of self-efficacy and, by analyzing it, to point to teachers’ existing strengths and weaknesses in the implementation of inclusive education. The sample consists of 148 teachers, 54.7% of whom are primary school teachers, and 45.3% are subject teachers. The research was conducted in five primary schools in Serbia. The Teachers’ Sense of Efficacy Scale - TSES/Long form was used for the purpose of this research. Overall answers of the teachers from our sample are within “I have quite a bit of influence” self-assessment framework in the Scale (AM 7.14, SD 0.66), with minimum self-efficacy assessment in “I have some influence”. Distribution of answers in the subscales is similar to the distribution of overall answers, but it is observed that in the subscale “Efficacy in Challenging Goals”, regardless of high arithmetic mean (AM 6.50, SD 1.09), minimum self-efficacy assessment is closer to “I have very little influence”. Teachers’ sense of self-efficacy is a construct which can significantly influence teachers’ readiness to work in a challenging environment, and as such, has to be included in considering the implications for the implementation of inclusive education. Key words: sense of self-efficacy, inclusive teaching